2016
DOI: 10.1086/686986
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Connecting, a Substance-Abuse Prevention Program for Foster Teens and their Caregivers

Abstract: Objective To test the feasibility, usability, and proximal outcomes of Connecting, an adaptation of a low-cost, self-directed, family-based substance use prevention program, Staying Connected with Your Teen, with foster families in a randomized, waitlist control pilot study. Method Families (n = 60) fostering teens between 11 and 15 years of age were recruited into the study and randomly assigned into the self-administered program with telephone support from a family consultant (n = 32) or a waitlist control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
1
4
0
1
Order By: Relevance
“…Given the lack of evidence-based prevention programs to address higher levels of risk behaviors among teens in foster care compared to teens in general, it is important to develop and test interventions specifically designed to support caregivers and youth in foster care that address the risk and protective factors associated with health risking behaviors such as substance use, delinquency, and adolescent sexual activity. Consistent with the social development model and earlier findings (Haggerty et al, 2016 , 2021 ), we hypothesized that Connecting would lead to a reduction in the youths’ involvement in high-risk behaviors. To that end, we tested the efficacy of a family-focused prevention program adapted from a universal prevention program based on the social development model which has been previously shown to reduce substance use, violent delinquency, and sexual initiation among adolescents.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Given the lack of evidence-based prevention programs to address higher levels of risk behaviors among teens in foster care compared to teens in general, it is important to develop and test interventions specifically designed to support caregivers and youth in foster care that address the risk and protective factors associated with health risking behaviors such as substance use, delinquency, and adolescent sexual activity. Consistent with the social development model and earlier findings (Haggerty et al, 2016 , 2021 ), we hypothesized that Connecting would lead to a reduction in the youths’ involvement in high-risk behaviors. To that end, we tested the efficacy of a family-focused prevention program adapted from a universal prevention program based on the social development model which has been previously shown to reduce substance use, violent delinquency, and sexual initiation among adolescents.…”
Section: Discussionsupporting
confidence: 65%
“…This suggests that the developmental timing of a self-directed, family-focused preventive intervention for caregivers of youth in foster care may have a stronger impact on risk behaviors that typically emerge in later adolescence as exposure to higher risks becomes more prevalent. Our previous work (Haggerty et al, 2016 ) has demonstrated that about half the caregivers refer back to the program materials over the course of time, suggesting ongoing use of the materials may be useful as environments become more risky. Thus, the availability of relevant, self-directed parenting guidance for foster caregivers caring for teens may be beneficial for reducing overall later risk-taking behaviors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…UU. El estudio del programa entre los niños en familias de acogida ha indicado el impacto positivo del programa Staying Connected with Your Teen®, en términos de una gestión familiar más sólida, una mejor comunicación entre los padres y el niño adolescente, una mayor participación de los adolescentes en el establecimiento de reglas familiares, y una disminución en las actitudes positivas de los adolescentes hacia el comportamiento antisocial (Haggerty, Barkan, Skinner, Packard, & Cole, 2016).…”
Section: Totalunclassified